Enhancing the photoelectrochemical performance of TiO2 photoanode by employing carbon nanoparticles as electron reservoirs and photothermal materials - Huang, Jing; Huang, Yijie; Guo, Puwen; Li, Yinchang (Frontiers in Chemistry, 2024)
Photoelectrochemical (PEC) water splitting is regarded as a potential technique for converting solar energy. However, the fast charge recombination and slow water oxidation kinetics significantly have hindered its practical application. It is found that an elevation in operation temperature can activate the charge transport in the photoanodes. Here, a strategy was performed that carbon nanoparticles were employed to TiO2 nanorods, acting as electron reservoirs as well as photothermal materials. More specifically, a record photocurrent density of 1.62 mA cm−2 at 1.23 V vs. RHE has been achieved, accompanied by a high charge separation efficiency of 96% and a long-term durability for 8 h. The detailed experimental results reveal that under NIR light irradiation, the synergistic effect between electron storage and temperature rise leads to accelerated charge transport in the bulk and water oxidation kinetics on the surface. This research offers a new perspective on how to boost the PEC performance of photoelectrodes.